Heavy Smoking and Tears Protein Pattern - Sariri, R.; Arasteh, A.; Mahmoodian, J. (Asian Journal of Chemistry, 2010)
In this research, the change in tear protein electrophoretic pattern in smokers, heavy smokers compared to non-smokers were investigated. The survey was conducted for 100 volunteers, out of which 50 were non-smokers, 25 smokers and 25 heavy smokers. The subjects, all male and aged 2030 years old, filled a table in order to get some information about their health and smoking history. Total tear proteins and lysozyme concentration were measured and the proteins separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDSPAGE). The results showed some alterations in tear protein pattern of smokers that was more noticeable in heavy smokers. The number of electrophoretic bands in tears of heavy smokers was about 25% more than of non-smokers. The changes observed in tear proteins of heavy smokers can explain the higher incidence of dry-eye syndrome observed in smokers.